Nutritional levels of digestible threonine in brown-egg laying hens from 75 to 90 weeks of age - Agustini, Márcia Antonia Bartolomeu; Nunes, Ricardo Vianna; Vilela, Christiane Garcia; Takahashi, Sabrina Endo; Vilela, Valter Oshiro; Bueno, Rachel Santos [UNESP]; Polese, Clauber (Universidade Estadual de Londrina, 2014)
An experiment was conducted in the Department of Experimental Stations of the Universidade Tecnológica Federal do Parana - UTFPR campus Dois Vizinhos - PR, with the objective of determining the nutritional levels of threonine for laying hens aged 75 to 90 weeks. One hundred fifty laying Shaver Brown pullets were used in a completely randomized design (CRD) submitted to a basal diet containing 2.85 kcal ME/g and 148.7 g/kg CP, supplemented with 4.6; 4.9; 5.2; 5.5 or 5.8 g/kg of digestible Lthreonine (98 %), which provided 0.000, 0.027, 0.058, 0.089 or 0.120% threonine, respectively. The feed conversion, egg production, egg weight, egg mass and internal egg quality were not affected (P> 0.05) by the threonine in the diet. The Haugh unit showed a linear effect with threonine consumption in that it increased levels of digestible amino acids in the diet. The variables percent albumin and shell showed quadratic effects, so the recommended dietary digestible threonine level was 5.20 g/kg, which corresponds to 0.648 g threonine/hen/day, and 5.25 g/kg, which is equivalent to 0.654 g threonine/hen/day, respectively. The specific gravity was affected by the level of threonine; the indicated level is 5.22 g/kg, equivalent to 0.651 g of threonine/hen/day obtained by the quadratic effect.
Keywords: Digestible amino acid; Egg quality; Performance